Analisis Analisis Pengaruh Layanan Sirkulasi Terhadap Kepuasan Pemustaka Pada Dinas Perpustakaan Dan Kearsipan Di Kabupaten Bengkayang - Oskar, Oskar Nanda Milen; Hermawan, Anton; Pramoekti Narendra, Albertoes (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2024)
This research aims to assess the influence of circulation services on patron satisfaction at the Bengkayang Library using a quantitative method. This method is considered scientific because it is rational, systematic, measurable, and objective. The study will depict the impact of circulation services on patron satisfaction at the Department of Library and Archives of Bengkayang Regency, employing statistical analysis through the SPSS data processing program version 26. The field study encompasses descriptive statistics involving research data, including an overview of respondents, research variables, measurement tool tests, and classical assumption tests. Ultimately, the research results indicate a positive correlation between circulation services and patron satisfaction. Incremental improvements in circulation services can enhance patron satisfaction at the Bengkayang Library. Questionnaire distribution results show that patrons are satisfied with circulation services, with an average score of 4.00 falling into the